P 145 Deficient body structural description in apraxia. Issue 10 (October 2017) - Dafsari, H. Salimi; Dovern, A.; Fink, G.R.; Weiss, P.H.
Abstract : Apraxia is a common cognitive deficit after left hemisphere (LH) stroke. It has been suggested that a disturbed representation of the human body underlies apraxic deficits. Thus, we here tested the hypothesis that a deficient body structural description (BSD), i.e., a deficient representation of a body part"s position (relative to a standard human body), contributes to apraxia, while controlling for a deficient semantic representation of the human body (body image, BI) and aphasia. A quantitative pointing task to assess putative BSD deficits and an apraxia assessment including imitation and pantomime tasks were applied to 27 patients with LH stroke and 19 healthy subjects. While LH stroke patients without apraxia ( n = 15) did not differ from control subjects in their pointing performance, apraxic patients ( n = 12) showed a differential deficit when pointing to body parts of other humans compared to object parts. Voxel-based lesion symptom mapping (VLSM) revealed an association of these differential pointing deficits (indicating a deficient BSD) with lesions in the angular gyrus of the left inferior parietal cortex. This first quantitative group study of BSD deficits in apraxia supports the notion that apraxia is – at least in part – due to a deficient coding of the position of human body parts.